New technology for cassava intercropping - Leihner, D.E. (International Center for Tropical Agriculture, 1979)
CIAT has developed a new intercropping technology (cassava/grain legume associations) that tries to solve the numerous problems that arise in traditional intercropping systems. High-yielding cassava cv. with an erect, late-branching growth habit are recommended to minimize intercrop competition. The legume species used (preferrably Phaseolus vulgaris, Vigna unguiculata, Arachis hypogaea) should be early-maturing, cover the ground rapidly and with determinate growth habit. The associated crops should be planted simultaneously, each at its normal monocropping density. An appropriate planting pattern should be determined, and diseases, insects and weeds adequately controlled. Further research is needed in the area of plant nutrition and mechanization of the intercropping system. (CIAT)